PENGARUH MEDIA LAGU TERHADAP HASIL BELAJAR SISWA MATERI MENGENAL HURUF DI KELAS I SD NEGERI 040454 PECEREN - Lovita Sari; Pelista Br Karo Sekali; Frida Dian Handini Lubis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low ability of first-grade students at SD Negeri 040454 Peceren in recognizing letters as the basic foundation for reading and writing. Based on the results of initial observations conducted by the researcher with the class teacher, out of 26 students there were 11 students (42.3%) who had not recognized letters well, 5 students (19.2%) who still had difficulties in reading, and only 10 students (38.5%) who were able to read properly. The learning process was still dominated by the lecture method and written assignments without the use of interesting learning media. This condition caused students to be less active, easily bored, and less focused during the learning process. In fact, first-grade elementary school students are still in the early development stage that requires fun, concrete, and activity-based learning. Therefore, learning media that can increase students' interest and learning outcomes are needed. One of the learning media used in this research is song media because songs have rhythm and repetition that can help students remember letters more easily. The purpose of this research was to determine whether there is an effect of using song media on students' learning outcomes in recognizing letters for first-grade students at SD Negeri 040454 Peceren in the 2025/2026 academic year. This research used a quantitative approach with a One Group Pretest–Posttest design. The research was conducted in the first semester of the 2025/2026 academic year. The population as well as the sample in this study consisted of all first-grade students at SD Negeri 040454 Peceren totaling 26 students. Therefore, the sampling technique used was saturated sampling. Data collection techniques were carried out through observation and learning outcome tests. The tests were given twice, namely before treatment (pretest) and after treatment (posttest). The research instruments were tested for validity and reliability to ensure their feasibility. The data obtained were then analyzed using the Shapiro–Wilk normality test and the Paired Sample T-Test with the help of the SPSS program. The results of the research showed an improvement in students' learning outcomes after using song media. The average pretest score was 68.34 and increased to 87.88 in the posttest. The results of the normality test showed that the data were normally distributed. Furthermore, the results of the Paired Sample T-Test showed a significance value (Sig. 2-tailed) of 0.01 < 0.05. This indicates that there is a significant difference between the pretest and posttest scores. Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Based on the results of the study, it can be concluded that the use of song media has a significant effect on students' learning outcomes in recognizing letters in first-grade students at SD Negeri 040454 Peceren in the 2025/2026 academic year. Song media can be used as an alternative learning method that is more interesting and helps students recognize letters better.